Can luxury brands be ethical? Reducing the sophistication liability of luxury brands - Pinto, Diego Costa (2022)
Pinto, D. C., Herter, M. M., Gonçalves, D., & Sayin, E. (2019). Can luxury brands be ethical? Reducing the sophistication liability of luxury brands. Journal of Cleaner Production, 233, 1366-1376. https://doi.org/10.1016/j.jclepro.2019.06.094